Effect of Pantograph’s Main Structure on the Contact Quality in High-Speed Railway - Jiangwen Wang; Guiming Mei (Shock and Vibration)
In general, the electrical energy is provided to the high-speed train through the pantograph-catenary sliding contact. The variation of the dynamic contact force is expected to be small enough to keep the good current collection quality and to extend the service life of the pantograph-catenary system. In this paper, the two tension wires of the catenary are discretized by the sine-series expansions, a multibody dynamics theory based on relative coordinates is adopted to describe the dynamic behavior of the pantograph, and the standard deviation (STD) of dynamic contact force is used as the indicator to evaluate the contact quality. The objective is to investigate how the variations of the pantograph’s main structure influence the contact quality, which may support the structural design and parameter optimization of the pantograph in high-speed railway.